Advances in rabies research - Germano, Pedro Manuel Leal (1994)
Recent advances in research into rabies, based on the technological process of the biological sciences mainly molecular biology and genetic engineering, are mentioned. The current knowledge of the characteristics, properties pathogeny and immunology of the rabies views is presented, as well as the development of new diagnostic and vaccine evaluation techniques. The epidemiological importance of the identification of different immunogenic rabies virus strains and the role in immunoprophylaxis of the production of highly immunogenic vaccines, are set out.